2020
DOI: 10.1016/j.gie.2020.04.048
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and personal protective equipment shortage: protective efficacy comparing masks and scientific methods for respirator reuse

Abstract: Background and Aims: The abrupt outbreak of the novel coronavirus disease 2019 and its rapid spread over many healthcare systems throughout the world has led to a shortage in personal protective equipment (PPE), which cannot be solved by reducing their use or by increasing production. It is thus necessary to promote PPE rational use, highlighting possible differences in terms of efficacy and promoting an effective technique to reuse them.Methods: A literature search was performed on PubMed, Scopus, Cochrane da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(135 citation statements)
references
References 11 publications
5
127
0
3
Order By: Relevance
“…On the other hand, an alternative to disinfection is the use of ultraviolet light, the use of which, however, is limited due to its high cost. 9,15,[30][31][32] Surfaces and objects used after care must be constantly disinfected to reduce the risk of cross-contamination. A large number of studies have shown that sodium hypochlorite at 0.1%-0.5%, 62-71% ethanol, and 2% glutaraldehyde are able to disinfect surfaces by decreasing virus load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, an alternative to disinfection is the use of ultraviolet light, the use of which, however, is limited due to its high cost. 9,15,[30][31][32] Surfaces and objects used after care must be constantly disinfected to reduce the risk of cross-contamination. A large number of studies have shown that sodium hypochlorite at 0.1%-0.5%, 62-71% ethanol, and 2% glutaraldehyde are able to disinfect surfaces by decreasing virus load.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26]33 Direct contact with disinfectants, such as alcohol and hypochlorite, may cause skin reactions, such as peeling, cracking, stinging, bleeding, and dermatitis; therefore, the use of protection is recommended for surface disinfection. 31 In addition, it is important to follow adequate waste management after dental consultation, categorizing the different types of waste into the corresponding packaging, providing better management by the staff responsible for waste disposal. 18,23,27,28 Moreover, because the appearance of COVID-19 is a recent phenomenon, more research is necessary to clarify the doubts remaining in relation to biosafety for dental offices and procedures and to establish definitive protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding efficacy as compared to N95 respirator are conflicting. 16,36,37 Combining with a face shield and eye protection maximizes protection. There are other respirator masks available but not all of them are equally efficacious, and many including the N95 require fit testing to ensure an adequate seal.…”
Section: Other Considerations During the Peak/ Resurgence Phasementioning
confidence: 99%
“…If viral testing is readily available, it is recommended that all patients undergo rapid nucleic acid based Real Time Reverse Transcriptase Polymerase Chain Reaction (RT-PCR)/antigen testing. 16 Ideally, these tests should be performed within 72 h of the procedure. 17 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this has also resulted in acute shortage of PPE. [ 1 ] The need of the hour is to minimize this shortage by decontaminating these respirators, so that they can be optimally reused. We already have evidence for Ultraviolet light and Hydrogen Peroxide (H 2 O 2 ) as a good source for decontamination of PPE.…”
mentioning
confidence: 99%